The contribution of the arts to interdisciplinary sciences: Art Therapy (Al-Academy, 2017)
The history of the arts is closely connected with the history of humankind, since it is impossible to separate our scientific and artistic advances’. Therefore, the current research focuses on the close bond between art and other disciplines. The connection of the arts to the sciences is unequivocal and undisputed; the contributions of artists to the various scientific domains are clear. If one scrutinises the ability of artists to participate in building societies, one will find that the arts have penetrated deeply into a range of products and inventions, starting with the pencil and ending with the missile. The artist’s contributions play a part in the minutest of details across all fields of industry: production, craftsmanship, medicine, tourism, education, architecture and media entertainment, to name just a few. This research sheds light on the interrelationship that exists between the domains of arts and art therapy by using the analysis-description method. The results have shown an integration of art into other domains and a strong connection between what is presented in the domain of art and the needs of art therapy. The research has concluded that it is necessary to extend the practice of arts beyond the realms of art colleges and public education where the practice of arts should be expanded into (including hospitals, youth centers, student activity centers and prisons), for arts have a role to play in meeting today’s challenges